From the mountains to the sea! Unusual swimming behavior in chamois Rupicapra spp. Issue 4 (3rd July 2020) - Kavčić, Krešimir; Corlatti, Luca; Rodriguez, Oscar; Kavčić, Borna; Šprem, Nikica
Abstract : The chamois is widely perceived as a strictly high-elevation ungulate, though its spatial behavior suggests fairly high phenotypic plasticity and long-range dispersal abilities. Here, we describe and discuss five events of 'unconventional' habitat use by chamois, i.e., individuals found swimming in the sea of Croatia and Spain, between 2004 and 2019. In four cases, sex, age, swimming distance and direction were recorded. The chamois were young males up to 5 years of age, with swimming distances of ca 300 to 3300 m. In Croatia, two individuals were found swimming across sea stretches and one towards the coast; in Spain the chamois was seemingly swimming towards the open sea. The reasons for such unusual behavior remain unknown. Although it might represent the outcome of a maladaptive combination of physiological needs (e.g., individual attempts to disperse) and constraining casualties (e.g., environmental or anthropogenic barriers), the limited information suggests caution in interpretation. Swimming behavior in chamois is not new. To our knowledge, however, this is the first reported information on the use of sea stretches, which suggests that even medium sized water courses and lakes are unlikely to fully block chamois movements.